Hematopoietic Stem Cell Heterogeneity - Jurecic, Roland (Adv Exp Med Biol, 2019)
Hematopoietic stem cells (HSCs) maintain lifelong production of mature blood cells and regenerate the hematopoietic system after cytotoxic injury. Use of expanding cell surface marker panels and advanced functional analyses have revealed the presence of several immune-phenotypically different HSC subsets with distinct self-renewal and repopulating capacity and bias toward selective lineage differentiation. This chapter summarizes current understanding of the phenotypic and functional heterogeneity within the HSC pool, with emphasis on the immune-phenotypes and functional features of several known HSC subsets, and their roles in steady-state and emergency hematopoiesis, and in aging. The chapter also highlights some of the future research directions to elucidate further the biology and function of different HSC subsets in health and disease states.